(untitled) (European Journal of Economics, Finance and Business Development, 2024)
In the development of an integrative partner of higher education and professional educational institutions, recommendations on Professional education, training of qualified specialists suitable for the labor market, specifics of professonal education, organization and management of educational processes in professional educational institutions are widely covered.